Magnetic material including ferrite pellets, method of manufacturing the same, and wireless charging device including the same

CN122940449APending Publication Date: 2026-10-20HYUNDAI MOTOR CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511169877.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-10
Filing Date
2025-08-20
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

虽然铁氧体磁片(tile)主要用于这种磁性垫,但是由于陶瓷磁片的高脆性特性,铁氧体磁片磁性材料容易受到冲击并且难以制造成三维形状

Benefits of technology

[0013]此外,该磁性材料可以抵抗外部冲击。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005557681620000101
    Figure BDA0005557681620000101
  • Figure BDA0005557681620000102
    Figure BDA0005557681620000102
  • Figure BDA0005557681620000111
    Figure BDA0005557681620000111
Patent Text Reader

Abstract

A magnetic material comprising ferrite granules, a method for manufacturing the same, and a wireless charging device comprising the magnetic material are provided. The magnetic material comprises 65 to 95 parts by weight of manganese-zinc (MnZn) ferrite granules and 10 to 25 parts by weight of MnZn ferrite powder. The method comprises synthesizing the manganese-zinc (MnZn) ferrite granules and mixing the MnZn ferrite granules with the MnZn ferrite powder. Synthesizing the MnZn ferrite granules includes mixing granular raw materials, calcining the mixed granular raw materials, pulverizing the calcined granular raw materials, and granulating the pulverized granular raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related applications

[0002] This application claims priority to Korean Patent Application No. 10-2025-0046508, filed with the Korean Intellectual Property Office on April 10, 2025, the entire disclosure of which is incorporated herein by reference. Technical Field

[0003] This disclosure relates to magnetic materials comprising manganese zinc (MnZn) ferrite pellets and MnZn ferrite powder, methods for manufacturing the magnetic materials, and wireless charging devices comprising the magnetic materials. Background Technology

[0004] With the increasing popularity of electric vehicles, there is growing interest in wireless charging technology, which enables battery charging without a wired charger. Wireless charging technology consists of a transmitter that transmits power and a receiver that receives the transmitted power; these transmitter and receiver components are composed of coils and magnetic materials. The magnetic material used is one of the key components determining the efficiency of wireless charging and is arranged in the form of a pad within the wireless charging device. While ferrite tiles are primarily used for these magnetic pads, the high brittleness of ceramic tiles makes ferrite tiles susceptible to impact and difficult to manufacture into three-dimensional shapes. Specifically, for the receiver portion (vehicle) of a wireless charging system for electric vehicles, the following drawbacks exist: the ferrite tile magnetic material may be easily damaged by vibration and external impacts during driving. To overcome these drawbacks, continuous efforts are being made to develop ferrite magnetic materials that resist external impacts while exhibiting excellent magnetic properties.

[0005] The descriptions in this background section are intended only to enhance the understanding of the background of this disclosure and should not be construed as an admission that they correspond to prior art known to those skilled in the art. Summary of the Invention

[0006] The following overview presents a simplified overview of some features. This overview is not exhaustive and is not intended to identify major or key elements.

[0007] This disclosure relates to providing magnetic materials comprising manganese-zinc (MnZn) ferrite pellets and MnZn ferrite powder having improved magnetic and strength properties, methods for manufacturing the magnetic materials, and wireless charging devices comprising the magnetic materials.

[0008] The magnetic material according to embodiments of the present disclosure may include 65 to 95 parts by weight of MnZn ferrite particles and 10 to 25 parts by weight of MnZn ferrite powder.

[0009] The wireless charging device according to embodiments of the present disclosure may include magnetic materials according to various embodiments of the present disclosure.

[0010] A method for manufacturing magnetic materials according to embodiments of the present disclosure may include synthesizing MnZn ferrite particles and mixing the MnZn ferrite particles with MnZn ferrite powder.

[0011] Synthesizing MnZn ferrite granules may include mixing granular raw materials, calcining and mixing granular raw materials, crushing and calcining granular raw materials, and granulating crushed granular raw materials.

[0012] By including not only MnZn ferrite powder but also MnZn ferrite particles, the magnetic materials according to embodiments of the present disclosure can exhibit improved permeability and magnetic properties.

[0013] In addition, this magnetic material can resist external impacts.

[0014] The magnetic material according to the embodiments of this disclosure can be manufactured by low-pressure thermoforming, which allows for an increase in the cross-sectional area of ​​the magnetic material. Therefore, it is possible to manufacture a large-area magnetic material with a size nine times greater than that of existing ferrite magnetic materials.

[0015] The magnetic material according to the embodiments of this disclosure can be manufactured using a forming pressure that is more than 80% lower than that of conventional ferrite magnetic sheets, thereby improving processing efficiency. Attached Figure Description

[0016] The foregoing and other aspects, as well as the following detailed description of the embodiments, should be better understood when read in conjunction with the accompanying drawings. However, this disclosure is not intended to be limited to the details shown in the drawings, and various modifications and structural changes may be made without departing from the spirit of this disclosure and within the scope and applicability of the equivalents of the claims. In the various drawings, the same reference numerals and symbols denote the same elements.

[0017] Figure 1 This is a graph showing the results of the tap density measurement of the granules according to Experimental Example 1.

[0018] Figure 2 This is a graph showing the results of the magnetic permeability measurement of the magnetic material according to Experimental Example 1. Detailed Implementation

[0019] Unless otherwise defined, all terms used herein (including technical and scientific terms) are those commonly used in the field to which the inventive concept of this disclosure pertains. It should be further understood that, unless expressly defined herein, terms in general use should also be interpreted as those commonly used in the relevant field, rather than in an idealized or overly formal sense.

[0020] While the terms “first,” “second,” and other numerical terms may be used herein to describe various elements, these elements should not be limited by these terms. These terms are used only to distinguish one element from another. For example, without departing from the scope of this disclosure, a first element may be referred to as a second element, and similarly, a second element may be referred to as a first element.

[0021] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting. As used herein, the articles “a,” “an,” and “the” include a plurality of indicators unless the context clearly indicates otherwise. In the following disclosure, the terms “comprising,” “including,” “having,” etc., specify the presence of features, steps, elements, and combinations thereof, but should not be construed as excluding or adding one or more other features, steps, elements, and combinations thereof.

[0022] The magnetic material according to embodiments of this disclosure may include manganese zinc (MnZn) ferrite granules and MnZn ferrite powder.

[0023] The magnetic material disclosed herein may comprise MnZn ferrite particles ranging from 65 to 95 parts by weight. If the particles are included in quantities less than 65 parts by weight, the magnetic properties of the magnetic material may deteriorate. If the particles are included in quantities greater than 95 parts by weight, the formability of the magnetic material may deteriorate. Therefore, the above range can be advantageous. The MnZn ferrite particles can have millimeter-scale dimensions and can be prepared by crushing the granular raw material and subsequently granulating the crushed material. MnZn ferrite particles can improve the magnetic permeability of the magnetic material.

[0024] In one embodiment, the MnZn ferrite particles can be spherical MnZn ferrite particles with a diameter ranging from 2 mm to 5 mm. If the particle diameter is less than 2 mm, the magnetic properties of the magnetic material may deteriorate. If the particle diameter exceeds 5 mm, the required thickness of the magnetic material may not be achievable. Therefore, the above-mentioned range can be advantageous.

[0025] The following provides a method for manufacturing this pellet and its detailed description.

[0026] The magnetic material disclosed herein may comprise 10 to 25 parts by weight of MnZn ferrite powder. If the powder is included in quantities less than 10 parts by weight, the formability of the magnetic material may deteriorate. If the powder is included in quantities exceeding 25 parts by weight, the magnetic properties of the magnetic material may deteriorate. Therefore, the above range may be advantageous.

[0027] According to embodiments of this disclosure, MnZn ferrite powder can have a diameter ranging from 35 μm to 90 μm. The powder can be obtained by removing impurities from a mixture comprising iron oxide, manganese oxide, and zinc oxide through a calcination process to produce a synthetic phase, followed by pulverization and drying.

[0028] According to embodiments of this disclosure, the magnetic material may further include fine MnZn ferrite particles. Fine particles can refer to particles with a size smaller than MnZn ferrite powder.

[0029] In one embodiment, the fine particles can have a diameter in the range of 4 to 15 μm. The fine particles can be produced by further pulverizing the MnZn ferrite powder.

[0030] In one embodiment, MnZn ferrite fine particles and MnZn ferrite powder may be included in a weight ratio ranging from 0:10 to 6:4. Magnetic materials according to embodiments of this disclosure can achieve various densities and other desired physical properties by including both MnZn ferrite powder and smaller-sized MnZn ferrite fine particles.

[0031] The magnetic materials according to this disclosure may further include an adhesive. The adhesive may be a liquid silicone adhesive. In one embodiment, the adhesive may be included in the range of 2.5 to 6 parts by weight. By including a liquid adhesive, the magnetic materials of this disclosure can exhibit excellent magnetic and strength properties. These effects are described in detail through the experimental examples below.

[0032] The magnetic material disclosed herein may be in the form of a pad.

[0033] The wireless charging device disclosed herein may include magnetic materials according to various embodiments of the present disclosure described above. In one embodiment, the wireless charging device may be a wireless charging device for electric vehicles.

[0034] The following describes a method for manufacturing magnetic materials according to the present disclosure.

[0035] The method for manufacturing magnetic materials according to this disclosure may include synthesizing MnZn ferrite particles and mixing the MnZn ferrite particles with MnZn ferrite powder.

[0036] Synthesizing MnZn ferrite granules may include mixing granular raw materials, calcining and mixing granular raw materials, crushing and calcining granular raw materials, and granulating crushed granular raw materials.

[0037] In the mixed granular raw material, the granular raw material may include iron oxide, manganese oxide and zinc oxide. In one embodiment, the granular raw material may include 65 to 75 parts by weight of iron oxide, 15 to 30 parts by weight of manganese oxide and 5 to 15 parts by weight of zinc oxide.

[0038] The calcination of the mixed granular raw materials can be carried out in the range of 800 to 1000°C. Through calcination, this disclosure can improve the sinterability and uniformity of the granular raw materials, and remove volatile impurities that will be generated during the calcination process described below.

[0039] The granular raw materials to be pulverized and calcined can be processed by wet milling. Through wet milling, the granular raw materials can be pulverized to a particle size of about 1 μm or smaller.

[0040] According to embodiments of this disclosure, after pulverizing and calcining the granular raw material, the method may further include adding an additive. The additive may be selected from CaO, Nb₂O₃, Co₃O₄, ZrO₂, SnO₂, Ta₂O₅, V₂O₅, and any combination thereof. This disclosure allows for the improvement of magnetic properties by using such additives.

[0041] According to embodiments of this disclosure, after adding the additive, the method may further include spray drying the granular raw material. In other words, after adding the additive to the pulverized granular raw material as described above, the material can be sprayed using a sprayer and dried by contact with high-temperature air. The granular raw material dried in this manner can be in granular form and can have a diameter of about 120 to 180 μm.

[0042] Following spray drying, the method may include granulating the granular raw material. In other words, the pulverized and dried raw material can be spherically shaped into granules of a few millimeters (mm) in size. During granulation, the granular raw material can be introduced together with water into a rotating drum and dispersed. The weight ratio of granular raw material to water can be 90 to 95:5 to 10. Furthermore, the circumferential speed of the drum rotor can be in the range of 85 m / min to 95 m / min. The inclination angle of the drum can be 50 to 65 degrees. ° Within the range.

[0043] According to embodiments of this disclosure, granulation of the granular raw material may further include calcining the raw material. Calcination of the raw material can be carried out in the range of 1200°C to 1350°C. In this disclosure, calcination of the raw material can completely ferritize the granules.

[0044] MnZn ferrite particles manufactured in this manner can be the same as those described above. In other words, MnZn ferrite particles can have a diameter ranging from 2 mm to 5 mm.

[0045] Furthermore, MnZn ferrite particles can have an apparent density ranging from 2.9 g / cc to 3.5 g / cc. If the apparent density of the particles is less than 2.9 g / cc, the magnetic permeability of the manufactured magnetic material may deteriorate, and higher formation pressure may be required when forming the magnetic material. If the apparent density of the particles exceeds 3.5 g / cc, the adhesion strength using the binders described below may decrease due to the reduced specific surface area, and the appearance properties and strength of the manufactured magnetic material may deteriorate.

[0046] When mixing MnZn ferrite granules with MnZn ferrite powder, a binder may be further included in the mixture. The binder may be the same as described above. In other words, the binder may be a liquid silicone rubber binder.

[0047] According to embodiments of the present disclosure, when mixing MnZn ferrite granules and MnZn ferrite powder, the MnZn ferrite granules can be mixed in the range of 65 to 95 parts by weight, the MnZn ferrite powder can be mixed in the range of 10 to 25 parts by weight, and the liquid silicone rubber adhesive can be mixed in the range of 2.5 to 6 parts by weight.

[0048] The present disclosure is described in more detail below through the following embodiments. However, the following embodiments and experimental examples are provided only for the purpose of describing the present disclosure in more detail, and the scope of the present disclosure is not limited to the following embodiments and experimental examples.

[0049] Example 1

[0050] Magnetic materials comprising MnZn ferrite particles and MnZn ferrite powder are prepared.

[0051] To synthesize MnZn ferrite granules, 70 parts by weight of iron oxide, 20 parts by weight of manganese oxide, and 10 parts by weight of zinc oxide were mixed. The mixture was calcined at approximately 900°C to remove volatile impurities. The calcined mixture was then wet-milled to produce small particles with a diameter of 1 μm or less. CaO, Nb₂O₃, Co₃O₄, ZrO₂, SnO₂, Ta₂O₅, and V₂O₅ were added to ensure magnetic properties, and the mixture was spray-dried to produce granules with a diameter of approximately 150 μm. To granulate the granules, the produced granules and water were introduced into a rotating circular drum at a weight ratio of 92:8. The circumferential speed of the drum rotor was set to the range of 85 to 95 m / min. The inclination angle of the drum was set to 50 to 65 degrees. °The range is as follows. Granulated particles are heat-treated at approximately 1300°C to fully ferrite-form them, thereby synthesizing the final MnZn ferrite particles.

[0052] 76.2 g of granules with a diameter of 4 mm and 19.0 g of MnZn ferrite powder with a diameter of 80 μm were prepared from the synthesized MnZn ferrite granules, and 4.8 g of liquid silicone rubber binder were mixed to prepare a slurry. The prepared slurry was filled into a mold with dimensions of width (70 mm) x length (70 mm) x height (5 mm), and then pressed using a press preheated to 120 °C at a speed of 0.40 tons / cm². 2 Pressed under pressure for 10 minutes to create magnetic materials.

[0053] Example 2

[0054] Magnetic materials comprising MnZn ferrite particles and MnZn ferrite powder were prepared in the same manner as in Example 1, except that MnZn ferrite particles with a diameter of 2 mm were used.

[0055] Example 3

[0056] Magnetic materials comprising MnZn ferrite particles and MnZn ferrite powder were prepared in the same manner as in Example 1, except that MnZn ferrite particles with a diameter of 3 mm were used.

[0057] Comparative Example 1

[0058] MnZn ferrite magnetic sheets excluding MnZn ferrite particles were prepared with the same dimensions as in Example 1.

[0059] Comparative Example 2

[0060] Magnetic materials comprising MnZn ferrite particles and MnZn ferrite powder were prepared in the same manner as in Example 1, except that a solid binder was used.

[0061] Experimental Example 1

[0062] In this experiment, the tap density of the MnZn ferrite particles used in Examples 1 to 3 was measured, and the magnetic permeability of the magnetic materials according to Examples 1 to 3 was measured.

[0063] For the compacted density, the aggregate was placed in a container, compacted regularly, and measured three times for each. The results are shown in... Figure 1 middle.

[0064] For the permeability (μ), the magnetic pads of the examples and comparative examples were processed into a ring shape (outer diameter 39mm × inner diameter 17mm × height 5mm), wound with 10 turns of Φ0.5 copper wire, and the inductance was measured using an LCR meter. The permeability was calculated based on the following formula, where L = inductance (μH), l = average magnetic path length (cm), N = number of turns, and A = cross-sectional area (cm²). 2 ).

[0065] Mode:

[0066]

[0067] The permeability was also measured three times, and the results were converted into a ratio relative to the vacuum permeability (relative permeability). Figure 2 As shown in the image.

[0068] refer to Figure 1 In Example 2, the density was measured to be approximately 3.5 g / cm³. 3 Up to 3.65 g / cm 3 Furthermore, in Example 3, the density was measured to be approximately 3.65 g / cm³. 3 Up to 3.95 g / cm 3 Example 1 has approximately 3.85 g / cm³. 3 Up to 4.1 g / cm 3 The density of the magnetic material increases with the size of the ferrite particles included in it.

[0069] See Figure 2 In Example 2, the relative permeability was measured to be approximately 25 to 28, and in Example 3, the relative permeability was measured to be approximately 28 to 43. Example 1 exhibited a relative permeability of approximately 40 to 50. These results confirm that as the size of the ferrite particles increases, both density and (relative) permeability increase, thereby improving the magnetic properties of the magnetic material.

[0070] Experimental Example 2

[0071] In this experiment, four samples of each of the magnetic materials in Example 1, Comparative Example 1, and Comparative Example 2 were prepared, and their strength was measured. For this purpose, a 300g steel ball was dropped from a certain height onto the magnetic material, and the height at which the magnetic material was damaged and the impact strength (J) were measured.

[0072] The results are shown in Table 1 below.

[0073] Table 1 shows the height of damage to magnetic materials and the corresponding impact strength.

[0074] Table 1

[0075]

[0076]

[0077] Referring to Table 1, Comparative Example 1 demonstrates an average impact strength of approximately 0.257 J and a minimum impact strength of less than 0.150 J. Comparative Example 2, using MnZn ferrite particles and a solid binder, shows an average impact strength of 0.551 J. In contrast, Example 1 shows an average impact strength of 0.771 J and a maximum impact strength of 0.882 J. These results confirm that further incorporating MnZn ferrite particles into existing sheet-type MnZn ferrite magnetic materials improves the strength of the magnetic material. Furthermore, these results confirm that liquid binders improve the strength of the magnetic material more than solid binders.

[0078] This disclosure has been specifically shown and described with reference to embodiments thereof. In this regard, those skilled in the art will understand that various changes in form and detail may be made therein without departing from the scope of this disclosure. Therefore, the disclosed embodiments should be considered descriptive rather than restrictive. The scope of this disclosure is not limited by the detailed foregoing description but by the appended claims, and all differences within the scope should be construed as including in this disclosure.

Claims

1. A magnetic material, comprising: MnZn ferrite granules in the range of 65-95 parts by weight; as well as MnZn ferrite powder in the range of 10-25 parts by weight.

2. The magnetic material according to claim 1, wherein, The MnZn ferrite particles are spherical MnZn ferrite particles with a diameter ranging from 2 mm to 5 mm.

3. The magnetic material according to claim 1, wherein, The MnZn ferrite powder has a diameter in the range of 35 μm to 90 μm.

4. The magnetic material according to claim 1, wherein, The magnetic material further comprises fine MnZn ferrite particles with a diameter ranging from 4 μm to 15 μm.

5. The magnetic material according to claim 4, wherein, The mixture comprises the fine MnZn ferrite particles and the MnZn ferrite powder in a weight ratio ranging from 0.1:9.9 to 6:

4.

6. The magnetic material according to claim 1, wherein, The magnetic material also includes a binder in the range of 2.5 to 6 parts by weight.

7. The magnetic material according to claim 6, wherein, The adhesive is a liquid silicone rubber adhesive.

8. A wireless charging device comprising the magnetic material according to claim 1.

9. A method for manufacturing a magnetic material, the method comprising: Synthetic MnZn ferrite granules; as well as The MnZn ferrite granules are mixed with MnZn ferrite powder. The synthesis of the MnZn ferrite particles includes: Mixed granular raw materials; Calcinated and mixed granular raw materials; Crushed and calcined granular raw materials; and The crushed granular raw materials are granulated.

10. The method according to claim 9, wherein, The granular raw materials include iron oxide, manganese oxide, and zinc oxide.

11. The method according to claim 10, wherein, The granular raw material includes: Iron oxides in the range of 65-75 parts by weight; Manganese oxides in the range of 15-30 parts by weight; and Zinc oxide in the range of 5-15 parts by weight.

12. The method according to claim 9, wherein, The calcination of the mixed granular raw materials is carried out in the range of 800 to 1000°C.

13. The method according to claim 9, wherein, Granulation of the pulverized granular raw material includes: The pulverized granular raw material and water are introduced into a rotating drum at a weight ratio of 90-95:5-10; and The pulverized granular raw material and water are dispersed in the rotating drum.

14. The method according to claim 9, wherein, The MnZn ferrite granules have a diameter in the range of 2 mm to 5 mm.

15. The method according to claim 9, wherein, The MnZn ferrite pellets have an apparent density in the range of 2.9 g / cc to 3.5 g / cc.

16. The method according to claim 9, wherein, The mixing of the MnZn ferrite granules and the MnZn ferrite powder further includes: mixing a liquid silicone rubber binder.

17. The method according to claim 16, wherein, The mixing of the MnZn ferrite granules and the MnZn ferrite powder includes the following steps: The MnZn ferrite granules range from 65 to 95 parts by weight; The MnZn ferrite powder, ranging from 10 to 25 parts by weight; and The liquid silicone rubber adhesive is in the range of 2.5 to 6 parts by weight.

18. The method according to claim 12, wherein, Additives are added to the pulverized granular raw material, wherein the additives are selected from CaO, Nb2O3, Co3O4, ZrO2, SnO2, Ta2O5, V2O5 and any combination thereof.

Citation Information

Patent Citations

  • Vehicle having internal antenna and external antenna and method for controlling thereof

    KR1020250046508A